2017
DOI: 10.1021/acs.energyfuels.7b01190
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Looping Hydrogen Generation Using Synthesized Hematite-Based Oxygen Carrier Comodified by Potassium and Copper

Abstract: Hematite has become a promising oxygen carrier (OC) due to its abundance and low cost for chemical looping hydrogen generation (CLHG). However, the poor redox reactivity, low yield, and purity of hydrogen are the main issues using hematite as an OC. In order to solve the problems, a synthesized OC based on iron ore comodified by copper and potassium was first proposed for CLHG to increase the reduction reactivity and hydrogen yield. Experiments were conducted in a batched fluidized bed reactor to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…It had been confirmed that the amount of copper adding deepened the reduction of Fe 2 O 3 , and the highest oxygen transport conversion and hydrogen yield of Fe10Cu8K1 also indicated the highest amount of metallic Fe and FeO in the oxygen carriers after reduction in our previous work. 21 Thus, it was more likely to deposit carbon on the oxygen carrier particles because of the large amount of Fe and FeO which were considered as catalysts for carbon deposition. 19,35,38 Fe10Cu5K1 is the suitable oxygen carrier with the highest resistance to carbon deposition among the prepared samples.…”
Section: Effect Of K and Cu Additive On Carbon Depositionmentioning
confidence: 99%
See 3 more Smart Citations
“…It had been confirmed that the amount of copper adding deepened the reduction of Fe 2 O 3 , and the highest oxygen transport conversion and hydrogen yield of Fe10Cu8K1 also indicated the highest amount of metallic Fe and FeO in the oxygen carriers after reduction in our previous work. 21 Thus, it was more likely to deposit carbon on the oxygen carrier particles because of the large amount of Fe and FeO which were considered as catalysts for carbon deposition. 19,35,38 Fe10Cu5K1 is the suitable oxygen carrier with the highest resistance to carbon deposition among the prepared samples.…”
Section: Effect Of K and Cu Additive On Carbon Depositionmentioning
confidence: 99%
“…Carbon formation possibly happens when the conversion of fuel and the reactivity of oxygen carrier are low . Much work has focused on developing the methods to enhance the redox rate of iron oxides . The common attempt to increase the reactivity of iron oxides is to introduce foreign additives.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28] Similarly, few studies have been reported in which the metals, Na, K, Cu and Ca etc., were implemented to enhance the reactivity of natural iron ores. Wang et al 29 reported that adding K and Cu had signicant effects on enhancing the reduction reactivity of hematite, as well as elevating the hydrogen production in the CLH production process. Liu et al 30 reported that the presence of K decreased the carbon deposition, and increased the reduction rate of iron ore and hydrogen yield in CLH production.…”
Section: Introductionmentioning
confidence: 99%